Music interventions to improve women’s health outcomes in the preconception, antepartum, intrapartum, and postpartum periods: An overview of reviews - Meighan Mary; Briana Kramer; Kirantheja Daggula; Anqi He; Sarah Clifford; Elizabeth Stierman; Kathryn Spielman; Porcia Manandhar; Andreea A. Creanga (PLoS ONE, 2026)
Aim To synthesize evidence from systematic reviews of interventions that employ music to improve women’s health outcomes in the preconception, antenatal, intrapartum, and postpartum periods. Methods Systematic reviews published between 2010 and 2025 that addressed music interventions for women in the preconception, antenatal, intrapartum, and postpartum periods were sourced from MEDLINE, Scopus, Embase, PsychINFO, and Cochrane Database of Systematic Reviews in March 2025. 754 systematic reviews were imported into Covidence software. Title-abstract screening, and full text review were conducted in duplicate by a team of 5 screeners. Data were extracted to summarize key characteristics and meta-analysis results. The methodological quality of the included reviews was assessed using the AMSTAR-2 tool. Risk of bias and GRADE quality assessments were extracted; when not reported, MM and BK assessed the risk of bias and quality of evidence. Results Aggregated findings from 20 reviews suggest that music interventions in the preconception, antepartum, and intrapartum periods have potential to alleviate anxiety (SMD ranging from −7.0 to −0.21), depression (SMD −3.67 to −0.51), and pain (SMD −2.70 to −0.92). Effects from implementation in the postpartum period appear more limited, albeit with a notable exception of demonstrated benefit in reducing depressive symptoms (SMD:-0.75; 95%CI:-1.47,-0.03). Interpretation of these findings warrant caution due to important methodological limitations related to widespread bias, heterogeneity, and imprecision in effect estimation. Conclusions Music interventions are a promising approach for women across the perinatal continuum of care. However, significant concerns with the methodological rigor of existing studies need to be addressed before implementation in clinical settings. Further research is critical to identifying design characteristics and implementation modalities of music interventions that most effectively improve women’s health outcomes. Strengthening the evidence on music interventions is vital to informing the effective integration of complementary and alternative medicine approaches into person-centered care strategies for women’s health.